Production and business performance of tilapia Oreochromis niloticus rearing in recirculation system with different stocking densities - Wichika Priatna; Tatag Budiardi; Iis Diatin (Jurnal Akuakultur Indonesia, 2026)
The increase in Nile tilapia (Oreochromis niloticus) production reflects a rise in fish consumption among the community. The provision of sufficient fry for ongrowing must accompany such a production boost. One way to achieve this is through intensification by increasing the stocking density of tilapia larvae during the nursery phase. This study aimed to analyze production performance and the economics of tilapia larva nursery in a recirculation system under different stocking densities. The experiment was carried out over 42 days using a completely randomized design with stocking density treatments of 5, 10, and 15 larvae per liter, each with five replicates. Differences in stocking density had a significant effect on absolute length growth rate (AGRL), specific length growth rate (SGRL), feed conversion ratio (FCR), and productivity. The 15 fish/L treatment yielded higher LPMP, SGR, and productivity than the other treatments, while showing the lowest FCR. It was concluded that the best production performance and economic return in a recirculating tilapia larva nursery system were achieved at 15 fish/L, delivering an annual productivity of 106,112 fish/m³, a revenue-to-cost ratio of 1.54, and a payback period of 0.65 years. Keywords: business analysis, fish tilapia, nursery, recirculation system, stocking density   Abstrak Peningkatan produksi ikan nila (Oreochromis niloticus) merupakan gambaran peningkatan konsumsi ikan di masyarakat. Peningkatan produksi perlu diikuti dengan penyediaan benih yang mencukupi untuk pembesaran. Upaya yang dapat dilakukan adalah dengan intensifikasi melalui peningkatan padat tebar larva nila pada tahap pendederan. Tujuan penelitian ini adalah menganalisis kinerja produksi dan usaha pendederan larva ikan nila pada sistem resirkulasi dengan padat tebar berbeda. Penelitian dilakukan selama 42 hari menggunakan rancangan acak lengkap dengan perlakuan padat tebar larva ikan nila, yaitu 5, 10, dan 15 ekor/L dengan lima ulangan. Perlakuan perbedaan padat tebar berpengaruh nyata terhadap laju pertumbuhan mutlak panjang (LPMP), laju pertumbuhan spesifik panjang (LPSP), rasio konversi pakan (RKP), dan produktivitas. Perlakuan padat tebar 15 ekor/L menghasilkan LPMP, LPSP, dan produktivitas yang lebih tinggi daripada perlakuan lain, sedangkan nilai RKP menunjukkan nilai terendah. Penelitian menghasilkan kesimpulan bahwa kinerja produksi dan usaha terbaik pada pendederan ikan nila bersistem resirkulasi dihasilkan pada padat tebar 15 ekor/L dengan memberikan produktivitas sebesar 106.112 ekor/m3 per tahun, revenue/cost ratio senilai 1.54, dan payback period yaitu 0.65 tahun. Kata kunci: analisis usaha, ikan nila, padat tebar, pendederan, sistem resirkulasi